Standardised Reporting Templates, Birads, Lirads, Impact on Clinical Decisions: A Systematic Review - Aanab Hayat, Samira Ahmad, Abbas Ahmad, Saira Khan, Salma Liaqat, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Organisational reporting systems like BI-RADS and LI-RADS standardise terminology and connect imaging inferences with administration, which can potentially change subsequent clinical decisions. Picture: To provide an evidence synthesis on the topic of whether BI-RADS/LI-RADS template-based reporting influences clinical decision-makingpen vs non-standardised narrative reporting. Methods: A systematic review following PRISMA 2020 guidelines was to be employed. Searches were conducted across major bibliographic databases and supplementary sources. Other eligible studies assessed BI-RADS and/or LI-RADS structured reporting with either a comparative (structured vs narrative) design or a before-and-after design and yielded decision-relevant outcomes. Appropriate tools to design specifically assess risk of bias were used, and findings narratively synthesised. Findings: Three studies were included in the review (1 BI-RADS, 2 LI-RADS). This continued to BI-RADS 3 pathways, where 32.0% had lost to follow-up, and those with an outcome, 8.6% were upgraded to BI-RADS 4/5 and biopsied with a yield of 1.7%. Interventions based on LI-RADS templates resulted in more category assignments documented, greater report integrity (31% reduced to 2% free-text to structured), and a higher rate of clinician-rated usability. Summary: Standardised BI-RADS/LI-RADS reporting leads to better report completeness and better decision-support communication, although there is little heterogeneous evidence on the direct changes in management. Keywords: BI-RADS; LI-RADS; structured reporting; narrative reporting; clinical decision-making; hepatocellular carcinoma; breast imaging